Siblings with typhoid fever: An investigation of intrafamilial transmission, clonality, and antibiotic susceptibility. Issue 34 (March 2020) - Meyer Sauteur, Patrick M.; Stevens, Marc J.A.; Paioni, Paolo; Wüthrich, Daniel; Egli, Adrian; Stephan, Roger; Berger, Christoph; Bloemberg, Guido V.
Abstract: Background: Typhoid fever usually manifests as an acute disease. However, asymptomatic carriage with Salmonella Typhi may occur. This study investigated a family setting of severe typhoid fever in Switzerland months after return from Bangladesh. Method: Standard microbiological procedures were performed. Testing for S . Typhi IgM antibodies was done using a novel immunochromographic lateral flow assay. Whole genome sequencing (WGS) followed by comparative core genome multilocus sequence typing (cgMLST) was performed on the S . Typhi isolates. Results: Four months after returning from a visit to Bangladesh sibling 1 (9 months) was diagnosed with a S . Typhi meningitis and sibling 3 (8 years) was identified as asymptomatic S. Typhi carrier. Sibling 2 (2 years) was retrospectively diagnosed with typhoid fever by IgM serology at the time point of admission to the hospital. Parents were asymptomatic and culture-negative. WGS analysis of family S. Typhi isolates showed clonality and strongest homology with S. Typhi strains occurring in Bangladesh. The S . Typhi strain showed resistance against fluoroquinolones. A 4-week course of ceftriaxone resulted in full recovery of sibling 1. S . Typhi was eradicated from sibling 3 following azithromycin treatment for 14 days. Conclusion: S . Typhi, acquired from a visit to Bangladesh, was most likely transmitted within the family from one brother as asymptomatic shedder to his 9-month-old brother who manifested S. Typhi meningitis as a very rare and life-threatening presentation of typhoid fever. S . Typhi infection should be considered even in case of uncommon manifestations and irrespective of the interval between disease presentation and travel to an endemic area.